(untitled) (Journal of Applied Learning and Teaching, 2020)
Recent research suggests there is a divergence of performance between UK and Chinese students as they progress through their degree. The current study uses a large dataset that includes sufficient detail to enable us to categorise students according to their previous educational experience to test for differential progression trajectories across a broader range of categories. We find that students who progress with identical grades subsequently experience a systematic divergence of performance that depends on the subject they are studying and their previous educational experience. Not only are inferior performance trajectories not restricted to Chinese students, but for more quantitative courses the performance of Chinese students frequently progresses at a rate that is comparable or superior to UK and other international students. The results not only contribute to our understanding of student achievement, but they also have practical implications for student recruitment, curriculum design and student support.